On the relationship between the Ikhwān sect in China and the Wahhābi movement in the Arabian Peninsula - Min, Keqin; Ma, Zhanming (Science Publishing Group, 2025)
This article is to clarify an intellectual obfuscation which since long has puzzled the scholars involved in the studies of Chinese Islam. For those scholars who always followed the view on the relationship between the Ikhwān in China and the Wahhābi movement in the Arabian Peninsula as the relationships of fountain source (the Wahhabi movement) and stream (the Chinese Ikhwan), which was firstly held by a Chinese Muslim scholar, Ma Tong, a pioneer researcher on this problem, have overlooked, I believe, the factual elements, such as time displacement, chronological sequence, opposing stand on theological tenets, different sources of reference books, different reform proposition and more, which are clearly analyzed in this study. Ma Tong’s and other pioneer researchers like Bai Shouyi’s and Feng Jinyuan’s role in this intellectual obfuscation is very important, because their works are only references available for the later researchers. With careful inference it is not difficult for one to find many fractures in their accounts. They linked Chinese Ikhwan with Arabia Wahabism simply because they believed that the latter was a popular movement when the Chinese imam Ma Wan-fu 马万福 (1853-1934), the founder of the Ikhwān sect, performed hajj, and afterwards stayed there on for furthering his studies for five years (from 1888 to 1893), before he returned to China. The Ikhwān sect was formally established in Monigou of Linxia, China, soon after that. Based on this sole connection, the upholders of the view of presupposed relations thought that the Ma Wan-fu’s Ikhwan must be influenced by Wahhābi movement during his five years stay in Mecca. However, some other scholars like Gao Wenyuan and others believed that there might be least connections between the two, but not source-stream relations, because they are clearly attached to two different ideological schools. This scholarly obfuscation has so far not been dealt with by any researchers. Thus, in this article we try to solve this scholarly conundrum from the six angles mentioned above, aimed at a firm conclusion that between the two movements there exist no source-stream nexus as upheld by many famed intellectuals